PENERAPAN MODEL PEMBELAJARAN SIKLUS PADA PELAJARAN IPA TERHADAP HASIL KOGNITIF SISWA KELAS VII SMP NEGERI 40 PEKANBARU - Siti Nurhasanah; Azizahwati Azizahwati; M. Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe students' cognitive learning outcomes with the application of learning models in the seventh grade of Pekanbaru State Middle School 40. The study was conducted in Odd Semester Academic Year 2018/2019. The research method used was Pre-Experimental design with the design of Intact Group Comparison. The research subjects consisted of 2 classes, in which class VII3 as the experimental class and class VII1 as the control class. In the learning process, the experimental class uses a 5E Learning Cycle model and a control class with a conventional model. Data collection using a written test in objective form (multiple choice) to see student learning outcomes in the cognitive domain. Data were analyzed using descriptive analysis techniques that are used to provide an overview of students 'cognitive learning outcomes including students' absorption of understanding concepts and learning effectiveness in temperature and heat material. The results showed that the average absorbency obtained by students in the experimental class was 6.09 higher than the absorption capacity of the control class. The conclusion of this study was: the application of the 5E cycle learning model (Learning Cycle) was more effective to improve student learning outcomes.Key Words: 5E learning cycle model, student cognitive results, temperature and heat.